2023
DOI: 10.1111/epi.17648
|View full text |Cite
|
Sign up to set email alerts
|

Functional evaluation of epilepsy‐associated KCNT1 variants in multiple cellular systems reveals a predominant gain of function impact on channel properties

Abstract: ObjectiveGain of function variants in the sodium‐activated potassium channel KCNT1 have been associated with pediatric epilepsy disorders. Here, we systematically examine a spectrum of KCNT1 variants and establish their impact on channel function in multiple cellular systems.MethodsKCNT1 variants identified from published reports and genetic screening of pediatric epilepsy patients were expressed in Xenopus oocytes and HEK cell lines. Variant impact on current magnitude, current–voltage relationships, and sodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…At the molecular level, different mechanisms underlying the enhanced channel functioning of GoF KCNT-1 variants have been proposed, among which are the following: the suppression of subconductance states together with changes in protein kinase C regulation [ 49 ]; changes in Na + sensitivity [ 55 ]; increased channel cooperative gating together with decreased single-channel conductance [ 56 ]; and altered interactions with binding partners [ 57 , 58 ]. Considering the GoF variants as the most pathogenic KCNT1 variants, during recent years, several efforts have been made by both academia and industry to discover KCNT1 blockers suitable as therapeutic tools for precision medicine.…”
Section: Potassium Channels: General Aspects and Involvement In Epilepsymentioning
confidence: 99%
“…At the molecular level, different mechanisms underlying the enhanced channel functioning of GoF KCNT-1 variants have been proposed, among which are the following: the suppression of subconductance states together with changes in protein kinase C regulation [ 49 ]; changes in Na + sensitivity [ 55 ]; increased channel cooperative gating together with decreased single-channel conductance [ 56 ]; and altered interactions with binding partners [ 57 , 58 ]. Considering the GoF variants as the most pathogenic KCNT1 variants, during recent years, several efforts have been made by both academia and industry to discover KCNT1 blockers suitable as therapeutic tools for precision medicine.…”
Section: Potassium Channels: General Aspects and Involvement In Epilepsymentioning
confidence: 99%
“…21−23 More than 60 distinct pathogenic variants have been reported in KCNT1, the vast majority of which prompt gainof-function (GoF) effects on KCNT1 channels, resulting in enhanced potassium currents when studied in heterologous expression systems in vitro. 24,25 Different molecular mechanisms leading to enhanced channel function have been identified, including: (1) changes in Na + sensitivity; 25 (2) increased channel cooperative gating; 26 (3) suppression of subconductance states; 14 (4) changes in protein kinase C regulation; 14 and (5) altered interactions with binding partners. 27,28 Seizures in patients with KCNT1-related epilepsy, particularly those with EIMFS or DEE phenotypes, are often highly refractory to pharmacological therapy.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Consistent with this role, loss-of-function (LOF) studies using mouse models lacking KCNT1, and the associated sodium-activated potassium (K Na ) current, have shown enhanced AP firing across multiple neuron types (Evely et al, 2017 ;Liu et al, 2022 ;Lu et al, 2015 ;Martinez-Espinosa et al, 2015 ;Reijntjes et al, 2019 ;Zhang et al, 2022 ). Characterizations of pathogenic DEEassociated KCNT1 variants in heterologous cells found that nearly all cause gain-of-function (GOF) effects on the channel, increasing the associated K Na current (Hinckley et al, 2023 ;Kim et al, 2014 ;McTague et al, 2018 ;Milligan et al, 2014 ;Tang et al, 2016 ). Based on LOF studies, this would be expected to reduce neuronal excitability; however, it is difficult to predict the effects of these GOF variants on AP generation in neurons, particularly among neuronal subtypes, a priori.…”
Section: Introductionmentioning
confidence: 99%